O suicídio na pauta do webjornalismo no Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2018)
This work addresses an analysis of the journalistic agenda in Amapá about suicide, from the perspective of the news portals. Amapá, G1 Amapá and SelesNafes.com. It seeks to under-stand how the vehicles can make a salutary approach on the subject, promoting the debate. In order to achieve these results, it consisted in the data collection of the occurrences of suicide in the state in the year 2017 and of the subjects made in that period. The work is necessary due to the importance and relevance of the subject in the mental health field in the present. The method used in this study was the quantitative, qualitative and content analysis proposed by Bardin, based on the correlation of the data with the theories agenda-setting, social-setting, newsworthiness and ethics. From the conclusion of this survey it was possible to arrive at a result concerning the reason why the amapaense press imoved itself to treat the cover on the suicide of a peculiar form.
Keywords: Webjornalismo - Amapá; Pauta; Portais de notícia; Suicídio; CNPQ::CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::JORNALISMO E EDITORACAO